The Non-Thrombotic Role of Platelets in Health and Disease - Kerrigan, Steve; Moran, Niamh (IntechOpen, 2015)
Platelets play a key role in thrombosis and haemostasis. However recent evidence clearly demonstrates that the functional role of platelets extends to many other processes in the body. With an internationally recognised list of contributing authors, The Non-Thrombotic Role of Platelets in Health and Disease, is a unique and definitive source of state-of-the-art knowledge about the additional role of platelets outside thrombosis and haemostasis. The intended audience for The Non-Thrombotic Role of Platelets in Health and Disease includes platelet biologists, microbiologists, immunologists, haematologists, oncologists, respiratory physicians, cardiologists, neurobiologists, tissue engineers, as well as students and fellows in these areas.